Methylation profile of selected TSGs in non-cancerous thyroid tissue adjacent to primary PTC - Migdalska-Sęk, Monika; Pastuszak-Lewandoska, Dorota; Czarnecka, Karolina; Nawrot, Ewa; Domańska, Daria; Brzeziński, Jan; Dedecjus, Marek; Brzeziańska, Ewa (Contemporary Oncology/Współczesna Onkologia, 2011)
Aim of the study : The aim of the study was to analyse the methylation profile of the eight tumour suppressor genes (TSGs) ARHI, CDH1, KCNQ1, MEST, p16INK4A, RASSF1A, SLC5A8 and VHL in noncancerous thyroid tissue adjacent to papillary thyroid carcinoma (PTC) and to assess whether it parallels the methylation level of the studied TSGs in the primary tumour. Material and methods : Thyroid tissue samples were obtained from patients with PTC from the centre of the primary lesion and the adjacent noncancerous tissue, macroscopically unchanged (n = 11). Genomic DNA was modified with sodium bisulfite and methylation-specific polymerase chain reactions (MSPs) were performed. For each studied TSG methylated and unmethylated MSP primers were designed. Quality and quantity of MSP products were assessed in automated electrophoresis. Results : Qualitative analysis revealed the presence of methylated and nonmethylated alleles both in PTC and normal thyroid tissue for all genes, except one ( KCNQ1 ). The highest methylation frequency was observed for AR HI, CDH1, p16INK4A, MEST and RASSF1A . Quantitative assessment confirmed a very high methylation level (MI values) for ARHI, CDH1 and RASSF1A . Methylation levels of the studied TSGs were only slightly higher in the PTC group. Conclusions : Alterations of TSG methylation levels in thyroid tissue may be considered as an early molecular event, specific not only for cancerous lesions. Epigenetic modifications of these genes may be of functional importance for thyroid carcinogenesis. On the other hand, it may be explained by the concept of field cancerization.